Design and Simulation Investigations of Stagger-Tuned W-Band Gyro-Twystron - Yadav S.G.; Akash; Thottappan M. (My University, 2025)
In the present article, a multi-cavity W-band gyro-twystron amplifier operating in fundamental TE01 mode has been designed, investigated for its beam-wave interaction behavior, and its performance has been enhanced by optimizing a diode type electron gun with a nominal velocity spread and stagger-tuning technique. The particle-in-cell simulation of the present gyro-twystron has predicted a peak RF output power of 84 kW with a saturated gain of 37 dB. The use of staggered RF cavities improved the bandwidth up to 1.5 GHz, which was found to be 2.5 times more than the synchronously tuned W-band gyro-twystron. The power conversion efficiency of the present stagger-tuned amplifier has been calculated as 22%. A single anode magnetron injection gun has been designed and modeled to form the gyrating electron beam with 65 kV, 6 A, and 4% velocity spread by using 2-D electron optics code. A collector with an effective collecting area and an output window have been designed and studied to extract the remaining energy of spent electrons and collect the RF power from the vacuum environment, respectively. © 1963-2012 IEEE.